Quadrature Rules and Iterative Method for Numerical Solution of Two-Dimensional Fuzzy Integral Equations - S. M. Sadatrasoul; R. Ezzati (Abstract and Applied Analysis)
We introduce some generalized quadrature rules to approximate two-dimensional, Henstock integral of fuzzy-number-valued functions. We also give error bounds for mappings of bounded variation in terms of uniform modulus of continuity. Moreover, we propose an iterative procedure based on quadrature formula to solve two-dimensional linear fuzzy Fredholm integral equations of the second kind (2DFFLIE2), and we present the error estimation of the proposed method. Finally, some numerical experiments confirm the theoretical results and illustrate the accuracy of the method.